Different remote realities: health and the use of territory in Brazilian rural municipalities - Aylene Bousquat; Márcia Cristina Rodrigues Fausto; Patty Fidelis de Almeida; Juliana Gagno Lima; Helena Seidl; Amandia Braga Lima Sousa; Ligia Giovanella (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To characterize remote rural Brazilian municipalities according to their logic of insertion into socio-spatial dynamics, discussing the implications of these characteristics for health policies. METHODS Starting from the category of analysis - the use of the territory - a typology was elaborated, with the delimitation of six clusters. The clusters were compared using socioeconomic data and the distance in minutes to the metropolis, regional capital, and sub-regional center. Mean, standard error and standard deviation of the quantitative variables were calculated, and tests on mean differences were performed. RESULTS The six clusters identified bring together 97.2% of remote rural municipalities and were called: "Matopiba," "Norte de Minas," "Vetor Centro-Oeste," "Semiárido," "Norte Águas," and "Norte Estradas." Differences are observed between the clusters in the analyzed variables, indicating the existence of different realities. Remote rural municipalities of "Norte Águas" and "Norte Estradas" clusters are the most populous, the most extensive and are thousands of kilometers away from urban centers, while those in "Norte de Minas" and "Semiárido" clusters have smaller areas with a distance of about 200 km away from urban centers. The remote rural municipalities of the "Vetor Centro-Oeste" cluster, in turn, are distinguished by a dynamic economy, inserted into the world economic circuit due to the agribusiness. The Family Health Strategy is the predominant model in the organization of primary health care. CONCLUSION Remote rural municipalities are distinguished by their socio-spatial characteristics and insertion into the economic logic, demanding customized health policies. The strategy of building health regions, offering specialized regional services, tends to be more effective in remote rural municipalities closer to urban centers, as long as it is articulated with the health transportation policy. The use of information technology and expansion of the scope of telehealth activities is mandatory to face distances in such scenarios. Comprehensive primary health care with a strong cultural component is key to guaranteeing the right to health for citizens residing in such regions.